Experiences of loneliness from childhood to young adulthood:study of the Northern Finland Birth Cohort 1986 - Rönkä, A. R. (Anna Reetta) (Oulun yliopisto, 2017)
Abstract Loneliness is a negative, involuntary, subjective, relational and sociocultural experience. Due to the multidimensional nature of the experience, this topic calls for research that explores loneliness on multiple levels. Drawing from different disciplines of the human sciences and utilizing a mixed methods approach, this study aims at contributing new knowledge of young peoples’ loneliness and exploring its meaning over time. Data for the study was drawn from the population-based Northern Finland Birth Cohort 1986 (NFBC1986) (N = 9,432). In three articles of the four included in this study, logistic regression analysis was used with samples of adolescents (aged 15–16; n = 5,817–7,014) who reported loneliness in the 2001–2002 adolescents’ questionnaire in order to explore what kind of associations loneliness has with different socioemotional, health, wellbeing and contextual factors. Girls reported loneliness more often than boys. Loneliness was associated with several adverse factors among adolescents, including deliberate self-harm, being bullied, dissatisfaction with life and feelings of unhappiness, sadness, and depression. School dislike was associated with loneliness only among girls. The findings from these quantitative articles and earlier loneliness theories informed the semi-structured interview guide utilized in data production for the fourth article. Qualitative data consisted of 35 interviews, conducted in 2013, selected from a sample of the same participants who reported being very lonely in the adolescents’ questionnaire. The study explored in what ways young adults (aged 27–28) described the experience of loneliness, how loneliness felt and what was the meaning of the experience over time. Based on qualitative, theory-guided content analysis, the experience of loneliness was described with five dimensions; Personal, Relational, Physical context, Life event and Sociocultural. The duration and intensity of loneliness fluctuated over the course of life and six loneliness trajectories were ...